Evolvable Machines Theory & Practice - Nedjah, Nadia; Mourelle, Luiza de Macedo (Studies in Fuzziness and Soft Computing, 2005)
Methods for the artificial evolution of active components, such as programs and hardware, are rapidly developing branches of adaptive computation and adaptive engineering. "Evolvable Machines" reports innovative and significant progress in automatic and evolutionary methodology applied to machine design. This book presents theoretical as well as practical chapters concentrating on Evolvable Robots, Evolvable Hardware Synthesis, as well as Evolvable Design.